Pengaruh Periklanan Terhadap Keputusan Nasabah untuk Menabung pada BNI Cabang Tasikmalaya - Muchamad Taufik; Apri Budianto; Irma Bastaman (Pajak dan Manajemen Keuangan, 2024)
The problems faced in this study include (1) How is advertising at BNI Tasikmalaya Branch? (2) What is the customer's decision to save at BNI Tasikmalaya Branch? (3) How does advertising affect the customer's decision to save at BNI Tasikmalaya Branch? This research aims to study, know, and analyze (1) Advertising at BNI Tasikmalaya Branch. (2) The customer's decision to save at BNI Tasikmalaya Branch. (3) The influence of advertising on the customer's decision to save at BNI Tasikmalaya Branch. The method used in this study is explanatory survey, while the technical data analysis is validity test, reliability test, descriptive statistics, Inferential Statistical Analysis with Simple Regression. The results of the study inform that (1) Advertising at BNI Tasikmalaya Branch is high. With the highest score on the sales response indicator and the lowest score on the persuasive influence indicator (pre/post preference testing). This means that advertising is heavily influenced by sales response indicators. (2) The customer's decision to save at Bank BNI Tasikmalaya Branch is very high. With the highest score on the customer compatibility indicator and the lowest score on the dramaturgy indicator. This means that the customer's decision to save at Bank BNI Tasikmalaya Branch is greatly influenced by customer compatibility indicators. (3) Advertising has a positive effect on the customer's decision to save at Bank BNI Tasikmalaya Branch. This means that if advertising is improved, then the customer's decision to save at Bank BNI Tasikmalaya Branch will also increase.